Assessing the clinical utility of volumetric HRCT in pediatric enlarged vestibular aqueduct related hearing loss. (April 2022) - Anand, Rohit; Stahl, Maximilian; Hicks, Kayla; Murray, Gail; Patel, Nirav; Gupta, Amit; Otteson, Todd
Abstract: Objectives: |The aim of this study was to evaluate the use of volumetric HRCT measurements in the diagnosis of enlarged vestibular aqueduct syndrome (EVAS) and describe the association of this novel radiographic approach with clinical hearing outcomes. We hypothesized that volumetric measurements may have stronger correlation to hearing loss given the anatomic variability of the vestibular aqueduct in linear measurements. Methods: A retrospective study design was used, including 51 patients that fit the inclusion criteria for the study for a total of 81 ears. 3D volumes were calculated using the MIM Software platform (MIM Software Inc.) from semiautomatic segmentation of the VA across individual slices on CT scan. Air and bone conduction data was collected from medical records with the air-bone gap being calculated from these data. Univariate and multivariate analyses were conducted to determine if volumetric VA size correlated with hearing loss outcomes. Results: Out of the study population, 30 subjects (58.8%) demonstrated bilateral EVA. Average VA size estimated by volumetric CT methodology was 0.035 mm 3 ; sd = 0.025 mm 3 . Volumetric measurements significantly correlated to both midpoint length and operculum size. Multivariate analysis adjusting for age, race, and gender demonstrated significant correlation between volumetric VA size and both low and high frequencies for PTA Air (p = 0.009; 0.010) and PTA Bone (p = 0.027; 0.002), respectively. Of note, the coefficient values for volumetric data were higher than linear measurements showing a potentially stronger correlation, albeit with high variability. Volumetric size was not significantly correlated to air-bone gap at either low or high frequency (p = 0.335; 0.062). Conclusion: Our results indicate that volumetric CT measurements of the VA may be a valid and viable new method for assessing EVAS patients. In our study, volumetric VA measurements demonstrated a strong correlation across both air and bone conduction at both frequency ranges measured, with potentially greater correlative strength than linear measurements.